Recurrent shock and pulmonary edema due to acetazolamide medication after cataract surgery - Zimmermann, S.; Achenbach, Susanne; Wolf, M.; Janka, Rolf Matthias; Marwan, M.; Mahler, V. (Heart & Lung, 2014)
We report a patient with recurrent shock and transient non-cardiogenic pulmonary edema within a period of two months - every time occurring after cataract surgery and a single oral dose of standard post-operative medication with acetazolamide.Records of the intensive care unit, review of the literature.This case demonstrates a rare but severe side effect of acetazolamide. We also present a review of the literature to raise the awareness of health care providers for this special form of non-cardiogenic pulmonary edema.
EVALuna2:11868